Determination of Kidney Length and Volume by Ultrasound in 100 Term Bangladeshi Newborn (Bangladesh Journal of Child Health, 2012)
Objective: To determine the normal range of kidney length and volume in term Bangladeshi newborn. Methods: Hundred inborn, healthy, appropriate for gestational ages, term infants were prospectively examined by sonography within 72 hours of birth by a single senior sonologist. In 52 boys and 48 girls body weight (BW), supine length (SL), occipito frontal circumference(OFC) were collected from delivery room records, and body surface area (BSA) was calculated using the formula BSA=BW(kg)0.425 ×BL(cm)0.725 ×0.007184 and BMI=Weight(kg)/height(m)2. Scanning was performed with 6.5 MHZ transducer with child supine position. Maximum length of each kidney was determined. Volume of the kidney was determined by the inbuilt formula of software. Kidney length and volume were then correlated with gestational age, body weight, length, OFC, body mass index (BMI) and body surface area of infant. Results: There were no significant differences in mean kidney length and volume between right (39.22±4.32 mm, 9.79±2.80cc) and left (38.36±4.30 mm, 9.82±2.24cc) and kidneys in boys (right kidney 39.77±4.28mm, 10.30±2.69cc, left kidney38.62±3.68mm, 9.91±2.06cc) and girls (right kidney 38.63±4.32mm, 9.23±2.83cc left kidney 38.09±4.91mm, 9.73±2.43cc). Kidney length was correlated better with BMI (